Laparoscopic or conventional ovariectomy in bitches: hemodynamic and pain assessment - Feranti, João Pedro Scussel; de Oliveira, Marília Teresa; de Souza, Fernando Wiecheteck; Hartmann, Hellen Fialho; Baumer, Sabrina; Soares, André Vasconcellos; Vaz, Marcos André Braz; Chaves, Rafael Oliveira; Libardoni, Renato do Nascimento; Brun, Maurício Veloso (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Feranti J.P.S., Oliveira M.T., Souza F.W., Hartmann H.F., Baumer S., Soares A.V., Vaz M.A.B., Chaves R.O., Libardoni R.N. & Brun M.V. [Laparoscopic or conventional ovariectomy in bitches: hemodynamic and pain assessment.] Ovariectomia laparoscópica ou convencional em cadelas: análise hemodinâmica e álgica. Revista Brasileira de Medicina Veterinária, 38(1):73-78, 2016. Departamento de Clínica de Pequenos Animais, Centro de Ciências Rurais, Universidade Federal de Santa Maria, Camobi, Santa Maria, RS 97105-900, Brazil. E-mail: mauriciovelosobrun@hotmail.com The purpose of this study was to compare hemodynamic and serum cortisol changes, as well as pain of two ovariectomy techniques (convencional versus laparoscopic) in bitches. In this trial, 17 young female mongrel dogs (12.58 ± 4.29 months-old, 10.16±0.69kg), were used. The animals were divided into two groups according to surgery. Median celiotomy approach for ovariectomy (OV) was carried out in eight animals of GC. Laparoscopic OV was performed in nine patients of the GV. To evaluate analgesia, hemodynamics parameters (HR, SAP, MAP, DAP, central venous pressure and cardiac output), serum cortisol and three pain scales (VAS, UMPS and Glasgow CMPS-SF). In both procedures (GV and GC) there were no complications during the surgery or in the postoperative period. Ovariectomy laparoscopic technique by two portals provided pain stimulus of lower magnitude and range, and rapid return to baseline cortisol values compared to the conventional approach, without affecting the hemodynamic parameters.